2019
DOI: 10.1016/j.cognition.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Compositional structure can emerge without generational transmission

Abstract: Experimental work in the field of language evolution has shown that novel signal systems become more structured over time. In a recent paper, Kirby, Tamariz, Cornish, and Smith (2015) argued that compositional languages can emerge only when languages are transmitted across multiple generations. In the current paper, we show that compositional languages can emerge in a closed community within a single generation. We conducted a communication experiment in which we tested the emergence of linguistic structure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 70 publications
5
40
2
Order By: Relevance
“…These findings are consistent with previous work investigating the independent effects of transmission (Kirby et al, 2008;Smith & Wonnacott, 2010) and interaction (Fay & Ellison, 2013;Theisen et al, 2010), as well as their combination (Kirby et al, , 2015 in the lab. We also suggest that our results are consistent with studies that have found systematicity to emerge without transmission (Nölle et al, 2018;Raviv et al, 2019;Winters et al, 2018). In theses cases, other manipulations (e.g.…”
Section: Experiments 1 Summarysupporting
confidence: 93%
“…These findings are consistent with previous work investigating the independent effects of transmission (Kirby et al, 2008;Smith & Wonnacott, 2010) and interaction (Fay & Ellison, 2013;Theisen et al, 2010), as well as their combination (Kirby et al, , 2015 in the lab. We also suggest that our results are consistent with studies that have found systematicity to emerge without transmission (Nölle et al, 2018;Raviv et al, 2019;Winters et al, 2018). In theses cases, other manipulations (e.g.…”
Section: Experiments 1 Summarysupporting
confidence: 93%
“…It is probable that the inclusion of communication and thus of the explicit goal of arriving at a shared system for communication results in conscious design by language users more than in Experiment 1. Nevertheless, the degree of structure increases as languages are transmitted through a learning bottleneck and thus, similarly to Theisen, Oberlander, and Kirby (2010) and Theisen-White et al (2011) in the graphic modality, results show that a certain degree of structure can emerge during communicative interaction but it is through iterated learning that it accumulates (see also Raviv et al 2018 for a similar cumulative effect with an expanding lexicon and a turnover of communicative partners) .…”
Section: The Effect Of Communicative Interaction In the Evolution Of supporting
confidence: 59%
“…Our findings reveal that when pressures to generalise and to be expressive are both present, languages become hierarchically compositional, which maximises the language's learnability without jeopardising its expressivity. Moreover, our study suggests that the trade-off between lernability and expressivity pressures is not only present intergenerationally in cultural transmission but also within a single generation during communicative interaction (Raviv et al 2018;Winters et al 2018). In comparison to an artificial pressure against ambiguity during individual production, the inclusion of communicative interaction facilitates the evolution of linguistic structure.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…While most iterated learning studies use the z-scores provided by the Mantel test for the correlation described above [43,44], z-scores were inappropriate for our design since they increase with the number of observations, and our meaning space expanded over rounds. Therefore, we used the raw correlations between meanings and strings as a more accurate measure of systematic structure [47,48].…”
Section: (Iv) Linguistic Structurementioning
confidence: 99%